Reaktualisasi Pendidikan Agama Islam untuk Anak dengan Gangguan Speech Delay: Reactualization of Islamic Religious Education for Children with Speech Delay Disorders - Ubaidillah, Ubaidillah (Absorbent Mind, 2023)
This research aims to actualize Islamic religious education for children with Speech Delay disorders. This type of research is a literature review. Data collection method with documentation from Google Scholar. Data analysis using a systematic literature review. The research results of the Reactualization of Islamic Religious Education for children with Speech Delay disorders are an important effort to ensure inclusivity and diversity in religious education. Through learning methods adapted to the needs of these children, such as the use of visualization, interactive media, and alternative communication approaches, this re-actualization aims to provide equal access to religious understanding and experience. With a more holistic and supportive approach, children with Speech Delay disorders can develop their religious skills while still paying attention to their special needs in communication.